Market-Oriented Reform of Foreign Trade in Planned Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper reviews the main features of market-oriented foreign trade reforms in planned economies. It considers reform initiatives aimed at expanding enterprise autonomy and breaking up the state monopoly of foreign trade, modifying the exchange rate system, and reforming the domestic price structure and ultimately the price system. The study emphasizes that the success of foreign trade reform, and therefore of a trade policy aimed at fundamental integration of planned economies into the world economic system, ultimately depends as well on the successful implementation of compatible reforms in the domestic economy as a whole.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet